2016
DOI: 10.1186/s13071-016-1648-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of 2-aminoalkanol and 1,2-alkanediamine derivatives against Strongyloides venezuelensis

Abstract: BackgroundStrongyloidiasis is a parasitic disease widely present in tropical and subtropical areas. Strongyloides stercoralis represents the main species that infects human beings. Ivermectin is the current drug of choice; however, issues related with treatment failure in patients with diabetes or infected with T-lymphotropic virus-1 make the identification of new molecules for alternative treatment a priority. In the present study, the activity of sphingosine-related aminoalcohol and diamine were evaluated ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…Currently, few anti- Strongyloides new drug research papers have been published; however, considering the small number, there is a great diversity of protocols used. Parameters evaluated in these papers include larvae survival, determined by parasite movement, and egg hatching ( Table 2 ) [ 16 , 17 , 22 , 24 , 25 ]. A few research groups showed promising in vitro results, as the activity of 2-(butylamino)hexadecan-1-ol, Newbouldia laevis essential oil, and Zanthoxylum zanthoxyloides essential oil against S. ratti and S. venezuelensis or Eryngium foetidum crude extract and Eryngial (trans-2-dodecenal) against S. stercoralis [ 16 , 21 , 22 ] ( Table 3 ).…”
Section: Models For Strongyloides Infection In mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, few anti- Strongyloides new drug research papers have been published; however, considering the small number, there is a great diversity of protocols used. Parameters evaluated in these papers include larvae survival, determined by parasite movement, and egg hatching ( Table 2 ) [ 16 , 17 , 22 , 24 , 25 ]. A few research groups showed promising in vitro results, as the activity of 2-(butylamino)hexadecan-1-ol, Newbouldia laevis essential oil, and Zanthoxylum zanthoxyloides essential oil against S. ratti and S. venezuelensis or Eryngium foetidum crude extract and Eryngial (trans-2-dodecenal) against S. stercoralis [ 16 , 21 , 22 ] ( Table 3 ).…”
Section: Models For Strongyloides Infection In mentioning
confidence: 99%
“…On the other hand, in vivo published data (summarized in Table 4 ) do not necessarily support results obtained in vitro. For example, in a study conducted by Legarda-Ceballos et al [ 16 ], out of four compounds with promising in vitro results, only one was capable of reducing mice parasite load in ~60%. Compounds derived from Piper tuberculatum , with known insecticide, trypanocidal, and fungicidal action, and compounds derived from Lippia sidoides , effective against some bacteria and Aedes aegypti larvae, were ineffective against S. venezuelensis in vivo.…”
Section: Models For Strongyloides Infection In mentioning
confidence: 99%
“…This strain was maintained by serial passages in Wistar rats routinely infected in the laboratory of Parasitic and Molecular Immunology, CIETUS, University of Salamanca. Rats were subcutaneously infected with third-stage larvae (L3) of S. venezuelensis, as previously described [20]. CD1 female experimental mice and maintenance rats were housed and maintained at the Research and Animal Welfare Service of the University of Salamanca under standard conditions, at a temperature of 24 • C and a humidity-controlled environment with 12 h day-night cycles and provided with water and food ad libitum.…”
Section: S Venezuelensis and Experimental Mice Modelmentioning
confidence: 99%
“…Compostos bioativos obtidos de plantas e seus derivados análogos sintéticos, como chalconas, alcaloides indólicos, aminoalcaloides e diaminas, cujos mecanismos de ação ainda não foram estabelecidos, são atualmente foco de discussões e pesquisas contra patógenos fúngicos de doenças humanas, que utilizam como premissa a potencialidade no controle e baixa toxicidade ao meio ambiente (ABENGÓZAR et al, 2015;LEGARDA-CEBALLOS et al, 2016;OLMO et al, 2016).…”
Section: Introductionunclassified
“…Legarda-Ceballos et al (2016), estudando doenças causadas por parasitas como Strongyloides venezuelensis, encontraram eficácia das diaminas in vitro e in vivo no controle do referido nematoide. Os mesmos autores, em 2015, observaram efeitos semelhantes no controle do protozoário Trypanosoma cruzi, com valores entre 10,8 e 19,2 µM de IC 50 .…”
unclassified